2001
DOI: 10.2214/ajr.177.2.1770309
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Thrombin Injection of latrogenic Femoral Pseudoaneurysms

Abstract: For the treatment of iatrogenic femoral pseudoaneurysms, thrombin injection under sonographic guidance is a quick and effective method of therapy. Failures and complications are infrequent. At our institution, sonographically guided thrombin injection has replaced compression repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
99
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 26 publications
5
99
0
4
Order By: Relevance
“…In the current study, the thrombosis rate was 69% (38 of 55 pseudoaneurysms) following a single injection and the primary therapeutic success rate (success rate of two injections) was 89% (49 of 55 pseudoaneurysms). Although the primary success rate (89%) was lower than in previous reports (1-3), the secondary success rate (96%) was similar to previous reports (1,2,4,6). No significant differences in success were observed with respect to pseudoaneurysm size (P = 0.30) and lobe number (P = 0.17).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the current study, the thrombosis rate was 69% (38 of 55 pseudoaneurysms) following a single injection and the primary therapeutic success rate (success rate of two injections) was 89% (49 of 55 pseudoaneurysms). Although the primary success rate (89%) was lower than in previous reports (1-3), the secondary success rate (96%) was similar to previous reports (1,2,4,6). No significant differences in success were observed with respect to pseudoaneurysm size (P = 0.30) and lobe number (P = 0.17).…”
Section: Discussionsupporting
confidence: 77%
“…This hole is rarely more than a few millimeters wide, which is likely too small for the passage of a large clot. If the thrombin itself leaked into the artery, it could be effectively neutralized by dilution and anticoagulant factors on the endothelium and in the circulating blood, such as thrombomodulin and antithrombin III (2,4,7). Thromboembolic complication occurs when an inadvertent injection of thrombin into the artery or injection is performed too close to the pseudoaneurysm neck.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare that embolectomy becomes necessary, but there are descriptions of subclinical embolization with percutaneous thrombin 14 . Distal embolization requiring surgery is described in around 2% of femoral pseudoaneurysm treatments 24 . Lewandowski et al found signs of distal embolization diagnosed clinically and on the basis of abnormal pulse oximetry in 30 to 38% of a sample 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Unresponsiveness to thrombin injection is an indication for open surgical repair. Side effects reportedly associated with thrombin injection include seizures, anaphylaxis (human thrombin may be less immunogenic than the bovine form), systemic activation of the coagulation system, risk of limb ischemia with intra-arterial injection, blue toe syndrome, groin abscess and crampy buttock pain (4).…”
Section: Discussionmentioning
confidence: 99%